Evaluation Report on Decentralised Experience of Kerala - Planning Commission (Planning Commission, 2006)
In Kerala, there have been many attempts at decentralization during the post- Independence period. Recent attempts to decentralize the planning process followed the 73rd and 74th constitutional amendments and enabling enactment in the State in 1994. The important landmarks in decentralization, inter alia, include the transfer of powers, functions, institutions and staff to local self-governments (LSGIs), adoption of separate budget document for LSGIs, decision to devolve 35 to 40% of the plan funds to LSGIs, launching of People’s Campaign in August 1996, institution-building at different tiers and levels, restructuring of the relevant State level Acts and Rules and submission of State Finance Commission Reports.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission Government of India